CORROSION RATE ANALYSIS AFFECTED OF POST WELD HEAT TREATMENT TO LIFE TIME OF PIPE IN PIPE API 5L GRADE B - KHOLIS NIM : 22209072); Pembimbing : Dr. Ir. Ucok W.R. Siagian, IKHSAN
Pipeline is widely used in oil and gas exploration. The installation can not be separated from the welding process. Where the welding process is one process that can affect the life time of pipe material. The problem that arises is the amount of the corrosion rate. Base on the facts, this thesis aims to find ways to extend the life time of pipeline in the connection are due to the welding process. Tests for heat treatment of PWHT on the pipe material API 5L PSL 1 Grade B uses variations of temperature 200 ° C, 250 ° C, 300 ° C, 350 ° C and 400 ° C with holding time 30 min and with air cooling. To complement the data of tests, it was conducted testing of micro photos, the testing of corrosion rate and the testing of macro photos. Three cell electrode with NaCl electrolyte solution is used in testing the corrosion rate. The test results of mirco-photograph showed that the compound of pearlite in the HAZ, base metal and weld metal in each test specimen increased along with the increasing of PWHT temperature. The value of corrosion rate on the specimen without heat treatment (28 º C) of 0.091703 mmpy, heat treatment 200 º C of 0.088025 mmpy, heat treatment 250 º C of 0.087290 mmpy, heat treatment 300 º C of 0.086589 mmpy, heat treatment 350 ° C of 0.085802 mmpy and heat treatment 400 ° C of 0.084979 mmpy. Addition of life time on the pipe material is taking place in specimens with temperatures above 200 º C. Temperature 400 º C is the most economical value of the heat treatment process. These results are obtained based on the amount of pearlite content, the corrosion rate, as well as the increase of the additional life time of pipe is 1 year and 3 months.